Kegiatan Skrining Gula Darah Dan Kolesterol Dalam Upaya Pencegahan Dini Diabetes Mellitus - Imelda Appulembang; Sofyan Sofyan; Trimaya Cahya Mulat; Susi Susanti (Sahabat Sosial: Jurnal Pengabdian Masyarakat, 2025)
Diabetes Mellitus (DM) is a non-communicable disease with a steadily increasing prevalence, especially in Indonesia. One early prevention effort is detection through regular blood sugar and cholesterol screening, particularly in adults. This community service activity aims to raise public awareness of the importance of early screening as a form of preventing the risk of DM. The activity was conducted in Village X and involved 110 participants aged 30–65 years. The screening included random blood sugar (BGS), total cholesterol, blood pressure, body mass index (BMI), and counseling on a healthy lifestyle. The results showed that 28% of participants had a BGS above the normal limit (>140 mg/dL), 36% had high cholesterol (>200 mg/dL), and 42% had a BMI in the overweight-obese category. After the education, 85% of participants reported an increased understanding of DM risk factors and the importance of regular check-ups. This activity has proven effective as a promotive and preventive measure to reduce the risk of DM in the community.